1989
DOI: 10.1007/bf00200802
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations and Intrinsic Chaotic and 1/f Dynamics in an Isolated Perfused Rat Heart

Abstract: The application of the theory of chaotic dynamical systems has gradually evolved from computer simulations to assessment of erratic behavior of physical, chemical, and biological systems. Whereas physical and chemical systems lend themselves to fairly good experimental control, biologic systems, because of their inherent complexity, are limited in this respect. This has not, however, prevented a number of investigators from attempting to understand many biologic periodicities. This has been especially true reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The rationale for the dimensional analysis of ECGs relies on a large collection of experimental and simulation results supporting the modelling of cardiac electrical activity as a nonlinear system (Glass et al 1983;Jensen et al 1984;Chialvo and Jalife 1987;Chee et al 1988;Savino et al 1989;Zbilut et al 1989). This approach offers a promising explanation to the intriguing contradiction between the sudden changes in rhythm observed on the ECG and the relatively slow variations in the overall cardiac state.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The rationale for the dimensional analysis of ECGs relies on a large collection of experimental and simulation results supporting the modelling of cardiac electrical activity as a nonlinear system (Glass et al 1983;Jensen et al 1984;Chialvo and Jalife 1987;Chee et al 1988;Savino et al 1989;Zbilut et al 1989). This approach offers a promising explanation to the intriguing contradiction between the sudden changes in rhythm observed on the ECG and the relatively slow variations in the overall cardiac state.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence that concepts from nonlinear dynamics are relevant in cardiac physiology comes from both experimental and theoretical studies. Experimental investigations on cardiac preparations of increasing complexity-from single cells to perfused whole heartshave shown, in response to electrical stimulation, the generation of complex patterns, typical of nonlinear systems, such as phase locking, period-doubling bifurcations and chaotic activity (Glass et al 1983;Chialvo and Jalife 1987;Savino et al 1989;Zbilut et al 1989;Chialvo et al 1990). Complex temporal or spatio-temporal patterns have also been described by computer simulations based on either the equations of membrane dynamics (Jensen et al 1984), or a formalized model of excitable medium (Moe et al 1964;Krinsky 1968;Smith and Cohen 1984;Chee et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that conventional statistical measures of this variability, such as the standard deviation, of intervals between normal heart beats have strong prognostic implications in patients with myocardial infarction (Kleiger et al 1987;Bigger et al 1988). Recently, there has been increased interest in more sophisticated ways of analysis of this variability, including methods of nonlinear dynamics (Mayer-Kress et al 1988;Babloyantz and Destexhe 1988;Lipsitz et al 1990) and spectral analysis as obtained by Fast Fourier Transform (FFT) (Kobayashi and Musha 1982;Saul et al 1987;Appel et al 1989;Zbilut et al 1989;Kleiger et al 1991;Bigger et al 1992). However, there are several problems in using FFT for spectral analysis of heart rate variability (HRV).…”
Section: Introductionmentioning
confidence: 99%
“…Our work has indicated that the rat heartbeat has a power law scaling of &2, and correlation dimension of &2 as would be expected of a random walk in time (Zbilut et al 1989). Transplanted human hearts, which do not have nervous system connections, also have power law scaling of &2 and dimensions of &2 (Zbilut et al 1988).…”
Section: Theorymentioning
confidence: 88%